KEKUATAN PEMBUKTIAN AKTA DI BAWAH TANGAN DALAM PERKARA PERDATA - Wulandari (LEGAL OPINION, 2024)
The author’s paper goal is to explain a deed under the hand . research method used are normatif. A deed under the hand is a deed made without the assistance of a public official, but made and signed by the parties only. A deed made under the hand is a writing that is deliberately used as evidence of events or occurrences and signed, where there is an important element, namely the intention to create written evidence and sign the deed. The necessity of a signature is intended to characterise or individualise a deed. As evidence in court proceedings, a deed under the hand does not have perfect evidentiary power because its truth lies in the signatures of the parties, which if recognised is perfect evidence like an authentic deed. Tujuan tulisan ini untuk menjelaskan akta di bawah tangan. metode yang digunakan yuridis normatif. Akta di bawah tangan adalah akta yang dibuat tanpa bantuan pejabat umum, melainkan dibuat dan ditandatangani oleh para pihak saja. Akta yang dibuat di bawah tangan adalah suatu tulisan yang sengaja dijadikan alat bukti tentang peristiwa atau kejadian dan ditanda tangani, ada unsur yang penting yaitu kesengajaan untuk menciptakan suatu bukti tertulis. Keharusan adanya tanda tangan adalah bertujuan untuk memberi ciri atau untuk mengindividualisir suatu akta. Sebagai alat bukti dalam proses persidangan di Pengadilan Akta di bawah tangan tidak mernpunyai kekuatan pembuktian yang sempurna karena kebenarannya terletak pada tanda tangan para pihak jika diakui merupakan bukti sempurna/autentik.